How Does MSME Tax Compliance Stand In Indonesia - Kusumastuti, Ratih; Nurlia; Suryadi, Dedy; Cakranegara, Pandu Adi; Apramilda, Riesna (Journal of Management, 2024)
The purpose of this study is to look at MSME taxpayer compliance while using tax socialization as a moderator. This study collects primary data by sending questionnaires to owners of Micro, Small, and Medium Enterprises located in East Java. Using a sampling approach known as convenience sampling, researchers were able to acquire 97 responses from the questionnaire. The data was examined using the SPSS tool, which included multiple linear regression model analysis. According to the results of the tests, tax incentives have no effect on taxpayer compliance; tax understanding has a positive effect on taxpayer compliance; tax socialization strengthens the influence of tax incentives on taxpayer compliance; and tax socialization weakens the influence of tax understanding on taxpayer compliance